The Portrait of Community Empowerment in Tamansari Village, Banyuwangi, in the Context of Social Innovation - Rusmaningsih, Prima Nurita; Kusumastuti, Retno (JPSI (Journal of Public Sector Innovations), 2023)
Community empowerment is designed to enhance economic development. Government programs that are usually top-down are now formulated to involve the active role of social innovation in the community. This research is focused on community empowerment through indigenous values. Bottom-up community empowerment, namely originating from joint decisions of community groups and for the welfare of the community, as well as assistance from the government, will have long-lasting value. With the indigenous value and indigenous knowledge they have, community groups develop the ability to analyze the condition of their communities and carry out action planning, where community groups are involved from the beginning of the process to the end. This research is intended to validate the community empowerment model of Tamansari Village, Banyuwangi, by using the PRA (Participatory Rural Analysis) concept in the tourism sector. The approach used in this study was post-positivist with qualitative data collection techniques, namely focus group discussions and interviews. The results showed that the community empowerment model in Tamansari Village contains a combination of social innovation and policy concepts. The combination is observed in seven dimensions, namely understanding, institutions, facilitators, implementation of community planning, community capacity building, productive economic business development, and training of community leaders as guides.